Analysis of the Difference in Level of Satisfaction of BPJS and Non BPJS Patients with Outpatient Services at the Tanjung Public Health Center - Bahrudin, Lalu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Health insurance is a guarantee in the health sector that is given to people who have paid contributions either by individuals or by the government. The issue that is developing in today’s society is that there are complaints about the lack of quality health services to patients using health insurance cards or BPJS, especially services at the Puskesmas level. The purpose of this study was to determine the difference in the level of satisfaction of BPJS health patients and non BPJS patients with outpatient services at the Tanjung Nusa Tenggara Barat Health Center. The research method using a cross-sectional study was carried out on 32 patients using BPJS health and 32 non BPJS patients, the qualitative sample in this study used 10 informants selected according to research needs, 4 informants from patients, 4 informants from health workers on duty, 1 doctor, and 1 representative informant from the leadership of the Puskesmas. The statistical test used was Mann-Whitney. The results showed that there was no difference in the level of satisfaction of BPJS health patients and non BPJS patients in the outpatient services of the Tanjung Nusa Tenggara Barat Health Center (p = 0.215; = 0.05). Overall there is no difference in the level of satisfaction of BPJS and Non-BPJS patients. Researchers also suggest that people can use BPJS health services as one of their future health insurance. In addition, the service elements of responsiveness and tangibles should still be maximized.